Pulmonary Artery Banding in a Cat with Atrioventricular Canal Defect Type A with Concurrent Muscular Septal Defect - Olga Szaluś-Jordanow; Krzysztof Zdeb; Wojciech Mądry; Michał Buczyński; Anna Świerk; Zofia Nowek; Agata Moroz-Fik; Michał Czopowicz (Animals)
Background: This case report describes the surgical management of pulmonary artery banding (PAB) in a cat diagnosed with an incomplete atrioventricular canal (AVC) defect and a concurrent muscular septal defect. It highlights the use of PAB as a palliative treatment to manage this rare congenital heart condition in companion animals. Case Presentation: A 9-month-old European long-haired male cat presented with clinical signs of heart failure. Pharmacological treatment with sildenafil and furosemide failed to stabilize the patient’s condition. Echocardiographic assessment revealed an incomplete AVC type A and a muscular septal defect. Pulmonary artery banding was performed to reduce pulmonary blood flow and alleviate heart failure symptoms. Pre- and postoperative echocardiographic evaluations were conducted to monitor structural and functional changes in the heart. Post-surgical outcomes included a marked reduction in the size of the right atrium and ventricle and a stable pulmonary artery flow velocity of 3.8 m/s. The cat has remained in very good condition without the need for pharmacotherapy for 13 months post-surgery and is still alive at the time of reporting. Conclusions: PAB proved effective as a palliative intervention for managing an incomplete AVC in this feline patient. The successful outcome suggests that PAB may offer significant long-term benefits and improved survival in selected cases of incomplete AVCs in cats.